Investigation of attitudes towards future of students taking sports education - Karademir, Mert; Karakaya, Yunus Emre (Ahmet DURMAZ, 2024)
This research was conducted to determine how the future attitudes of university students receiving sports education are shaped depending on the demographic variables discussed. The population of the research consists of students studying at the Sports Sciences Faculties of universities in the 2023-2024 academic year. The sample group consists of students studying at the Sports Sciences Faculties of Fırat University, Kahramanmaraş Sütçü İmam University and Çanakkale Onsekiz Mart University and who want to participate in the research on a voluntary basis. Sample group consists of a total of 602 students. In the research, in order to obtain the opinions of the sample group and collect data, a personal information form created by the researcher himself, as well as an attitude scale towards the future consisting of four sub-dimensions, was used. Analyzes of the quantitative data obtained from the scale form used were made with the licensed SPSS 22.0 package program. In the future attitude scale of the research, a statistically significant difference was found in the variables of university students receiving sports education, age ve marital status (p0.05). In addition, in line with the data obtained from the research group, it was determined that there was a positive linear, medium, high and very high level relationship between the sub-dimensions of the attitude towards the future scale, and this was also statistically significant. As a result, it has been concluded that the attitudes of university students who receive sports education towards the future differ according to the university they study at, their age ve marital status, and that their attitudes towards and profession do not affect their attitudes towards the future. In addition, it has been concluded that being positive, optimistic, open to innovations and having positive thoughts about managing the future also have positive reflections on their attitudes towards the future.

Bu araştırma, spor eğitimi alan üniversite öğrencilerinin geleceğe yönelik tutumlarının ele alınan demografik değişkenlere bağlı olarak nasıl şekillendiğini belirlemek amacı ile yapılmıştır. Araştırmanın evrenini 2023-2024 eğitim ve öğretim yılında üniversitelerin Spor Bilimleri Fakültelerinde eğitim ve öğrenim gören öğrenciler oluşturmaktadır. Örneklem grubunu ise Fırat Üniversitesi, Kahramanmaraş Sütçü İmam Üniversitesi ve Çanakkale Onsekiz Mart Üniversitesinin Spor Bilimleri Fakültelerinde öğrenim gören ve araştırmaya gönüllülük esası ile katılan öğrenciler oluşturmaktadır. Örneklem grubu toplam 602 öğrenciden oluşmaktadır. Araştırmada veri toplamak amacı ile araştırmacının kendisi tarafından oluşturulan kişisel bilgi formunun yanı sıra dört alt boyuttan oluşan geleceğe yönelik tutum ölçeği kullanılmıştır. Kullanılan ölçek formundan elde edilen nicel verilerin analizleri lisanslı SPSS 22.0 paket programı ile yapılmıştır. Araştırmanın geleceğe yönelik tutum ölçeğinde spor eğitimi alan üniversite öğrencilerinin eğitim aldıkları üniversite, yaş, medeni durumu değişkenlerinde istatistiksel olarak anlamlı fark bulunmuştur (p0.05). Ayrıca araştırma grubundan elde edilen veriler doğrultusunda geleceğe yönelik tutum ölçeğinin alt boyutları arasında pozitif yönde doğrusal, orta, yüksek ve çok yüksek düzeyde ilişki olduğu bunun da istatistiksel olarak anlamlı olduğu belirlenmiştir. Sonuç olarak, spor eğitimi alan üniversite öğrencilerinin geleceğe yönelik tutumlarının okudukları üniversite, yaş ve medeni durumlarına göre farklılık oluşturduğu, mesleğe yönelik tutumlarının ise geleceğe yönelik tutumlarına etki etmediği sonucuna ulaşılmıştır. Ayrıca olumlu, iyimser, yeniliklere açık olma ve geleceği yönetme düşüncelerinin olumlu olmasının aynı şekilde geleceğe yönelik tutumlarına da olumlu yansımalar gösterdiği sonucuna ulaşılmıştır.
Spor eğitimi alan öğrencilerin geleceğe ilişkin tutumlarının araştırılması
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi